Seafood Processing By-Products by Membrane Processes - Abejon-Elias, R (Elsevier, 2022)
Seafood wastes represent a demanding challenge for the seafood processing industrial sector due to their potentially harmful impact on the environment when not properly managed. Membrane-based processes, thanks to their intrinsic properties, must be considered as a valid alternative for the valorization of these wastes according to the principles of a sustainable circular economy. This work presents a review of the most significant applications of membrane technologies for the recovery of by-products from seafood processing wastes, taking into account the most important research trends and the most promising options in the production of new chemicals and materials. Membrane processes are a technically efficient and environmentally friendly option for the separation, fractionation, and purification of bioactive compounds for nutraceutical purposes and other valuable chemicals from seafood wastes. © 2022 Elsevier Inc. All rights reserved.